The Application Of Web-Based Online Parking Reservation - Rezky Ario Akuba; Teddy Siswanto (Penerbitan Universitas Trisakti, 2021)
The availability of parking lots being unresolved problems on the campus of Trisakti University because of the many civitas akademika which carries cars and limited parking. Parking system in use today is still the conventional with the regulations by parking attendants. For it is required an online parking reservation application system based web in addressing these barriers. The design of this system using the method Waterfall in the development of the system.Research methods the Analysis consists of a Waterfall will analyze problems and needs through the collection of data for the application of web-based online parking reservation, then proceed with the Design phase to make the draft application the system interface. Model design of engineering system using Activity diagrams, Use Case diagrams, Sequence Diagrams, and Class diagrams.From the results of the performed system design there are three actors, namely, the first User who can see the availability of the parking lot to do a parking reservation, among others, can choose the dates, hours, and parking lots so as to obtain a unique code to enter parking . The second is the actor who can do Admin input availability of parking in any parking area is available to perform a unique code input arrival and unique code input out of the user to receive parking costs which have been calculated from the system. The third actor i.e. Owner can perform the input the date, the hour, the land, types of vehicles, parking fee and can see the transaction reports. Class diagrams are formed is User, reservations, deals, Timeline, Rates for parking, and the type of vehicle.